TURBULENCE CLOSURE MODELLING OF SEDIMENT TRANSPORT BENEATH LARGE WAVES - Li Z.; Davies A.G. (My University, 2001)
The development of reliable coastal sediment transport and morphological models depends upon accurate parameterizations of sand transport processes. Here, an existing, local, one-dimensional vertical (1DV), one-equation turbulent kinetic energy (k) numerical model is extended to study the effects of (i) graded sediment sizes, (ii) turbulence damping and (iii) hindered settling, on the suspended sediment concentration beneath large symmetrical waves, and also on sediment transport rates beneath large asymmetrical waves. The aim of the paper is to explore these effects initially in isolation, and then in combination with one another. Size gradation is treated simply by dividing the bed material into volumetrically equal fractions, and modelling the response of each fraction; turbulence damping is represented primarily by a flux Richardson number correction; while hindered settling is represented by a simplified correction to the settling velocity for grains in isolation. The inclusion of all three physical processes is shown to lead to an improvement in predictive capability of the extended model compared with the one-equation k-closure model discussed by Davies and Li (Continental Shelf Res. 17 (5) (1997) 555-582).
Keywords: SEDIMENT TRANSPORT; LARGE WAVES; MODELLING